2007
DOI: 10.1111/j.1445-5994.2007.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural orthostatic tachycardia syndrome: an underrecognized disorder

Abstract: POTS is an underrecognized but persistent autonomic disorder in young patients with a variety of symptoms and variable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Moreover, symptoms of POTS range from well-recognized orthostatic dizziness and palpitation, to less recognized symptoms, such as fatigue, gastrointestinal dysfunction, and increased sweating. [ 12 , 13 ] These less recognized non-orthostatic symptoms could be unnoticeable without clinical suspicion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, symptoms of POTS range from well-recognized orthostatic dizziness and palpitation, to less recognized symptoms, such as fatigue, gastrointestinal dysfunction, and increased sweating. [ 12 , 13 ] These less recognized non-orthostatic symptoms could be unnoticeable without clinical suspicion.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of POTS is estimated at 0.2 % in the general population [ 1 ]; however, the exact prevalence remains unknown. POTS is still considered to be an under-recognized disorder [ 12 ], and its clinical significance is increasing, as it has been reported to be frequently accompanied by depression [ 11 , 14 ], sleep problems [ 15 ], chronic fatigue syndrome [ 16 , 17 ], and diminished quality of life (QOL) [ 15 , 18 ]. However, it is not known if depression or deterioration of QOL occurs frequently in patients with minimal OI symptoms despite excessive orthostatic tachycardia (OT).…”
Section: Introductionmentioning
confidence: 99%
“…Orthostatic intolerance is the main characteristic of POTS, 15 and can manifest as a variety of symptoms such as headache, dizziness, nausea, lightheadedness, blurred vision, palpitations, tremors, and difficulty concentrating. 4,15 It has been reported that the degree of orthostatic HR increment is not directly correlated with clinical symptoms, probably due to the diurnal variability of orthostatic tachycardia. 3 However, the severity of orthostatic intolerance symptoms is significantly correlated with depression and QOL.…”
Section: Orthostatic Intolerance Symptoms In Potsmentioning
confidence: 99%
“…1,2 POTS not only causes the well-recognized symptoms of dizziness and palpitation, but also various other symptoms including headache, fatigue, profuse perspiration, blurred vision, difficulty concentrating, and gastrointestinal discomfort. 3,4 The clinical significance of POTS has recently increased with findings of associations with depression, 5,6 sleep disturbance, 7 chronic fatigue syndrome, [8][9][10] and diminished quality of life (QOL). 7,11 Despite the increased prevalence of POTS reported over the past 2 decades due to the increased awareness of this syndrome, 1 it is still considered an underdiagnosed disease and deserves more attention from clinicians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation